Soft nuclear equation-of-state from heavy-ion data and implications for compact stars - Sagert, Irina; Chatterjee, Debarati; Schaffner-Bielich, Jürgen (Physical review. C, Nuclear physics, 2012)
Measurements of kaon production at subthreshold energies in heavy-ion collisions point to a soft nuclear equation of state for densities up to two to three times nuclear matter saturation density. We apply these results to study the implications on compact star properties, especially in the context of the recent measurement of the two solar mass pulsar PSR J1614-2230. The implications are twofold: First, the heavy-ion results constrain nuclear matter at densities relevant to light neutron stars. Hence, a radius measurement could provide information about the density dependence of the symmetry energy which is a crucial quantity in nuclear physics. Second, the information on the nucleon potential obtained from the analysis of the heavy-ion data can be combined with restrictions from causality on the nuclear equation of state. From this we can derive a limit for the highest allowed compact star mass of three solar masses.